Uwagi na temat konstrukcji podstaw prawnych współpracy transgranicznej jednostek samorządu terytorialnego - Kusiak-Winter, Renata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The more general the binding international and European law norms get, the more significant for trans-border cooperation national law norms become. Therefore, the effectiveness of cooperation is dependent on the compatibility of administrative and legal regulations concerning cooperating public entities when the regulations are simultaneously in force on both sides of a border. In this paper such a phenomenon is referred to as “co-existence” of two administrative law orders. Trans-border general agreements signed by local government units are based on similarities in competencies and structures present in administrative laws of both countries.
Keywords: principle of territoriality; cross-border contract; territorial self-government; administrative law; cross-border cooperation